HISTOLOGICAL, HISTOCHEMICAL AND SCANNING ELECTRON MICROSCOPIC STUDIES ON INTESTINE OF FRESHWATER CATFISH Horabagrus brachysoma (GUNTHER, 1864), EMPHASIZING ON GUT-ASSOCIATED LYMPHOID TISSUE - BOBINA, C. V.; PRASAD, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The intestine of threatened yellow catfish, Horabagrus brachysoma, was subjected to histological, mucin histochemical and surface ultrastructural analyses in the present study. Routine histological techniques were adopted, staining the sections with haematoxylin and eosin, periodic acid-Schiff and Alcian blue. Scanning electron microscope (SEM) analysis of intestine was conducted. The work revealed four histological layers of the intestine, similar to that of other catfishes. Goblet cells staining positive for neutral and acidic mucins were reported during histochemical studies. SEM observations showed that the mucosal surface of intestine was characterized by the presence of long, irregular wavy folds with microridge pattern of epithelial cells and goblet cells with expelled mucin droplets. The study focused on understanding the nature of gut‐associated lymphoid tissue (GALT) in the catfish. Intestine in H. brachysoma demonstrated GALT, consisting of diffuse populations of cells such as lymphocytes, granular cells, macrophages and plasma cells, as intraepithelial leucocytes (IELs) and as intralaminal leucocytes (ILLs). Accumulation or aggregation of lymphoid cells was not observed in the catfish intestine. These immune cells indicate the presence of GALT and, together with the secreted mucus, act as the first line of defence against pathogens in gut.